Balance between Metabolite Accumulation and Transport in Relation to Photosynthesis by Isolated Spinach Chloroplasts - Flügge, U. Ingo (1980)
The relationship between the rate of orthophosphate (Pi) transport into the stroma and the rate of CO(2) fixation by intact chloroplasts was investigated. High Pi concentrations in the medium lead to a depletion of stromal metabolites, due to excessive Pi transport into the stroma, resulting in the inhibition of CO(2) fixation. This inhibitory effect of Pi is released by inhibitors of Pi transport, such as pyrophosphate, citrate or pyridoxal-5-phosphate. The latter compound appeared to be specially valuable in inhibiting Pi transport without affecting stromal reactions. The Pi optima of CO(2) fixation were studied when the rate of CO(2) fixation or the rate of Pi transport was varied by the application of specific inhibitors. For optimal performance the rates of CO(2) fixation and Pi transport have to be matched in such a way, that transport neither limits nor exceeds CO(2) fixation. This accounts for the large variation in the Pi optima for CO(2) fixation by different chloroplast preparations.